O diário de leitura : um aliado para leituras literárias - Nascimento, Dorinaldo dos Santos (2015)
Face the deficit manifestations in literary reading associated with the narrowing and "erase" the place of the literary text in elementary school. Developed an action research through didactic sequence, favoring the use of daily reading as a tool with potential for intervention and data collection. The pilot application was with 9th grade students in a school of public municipal system (Banzaê-BA). Therefore, objective with this report to present and analyze the read daily paper in the literary text apprehension process (recording and sharing). It emphasizes that the practice diarist, adopted here, only materializes fully in their socialization, whose reading circle is an effective community of readers (the class). For the purpose of teaching literature, must not be confused with the daily reading the diary - Private genre in which the holder, individual space, records intimate revelations and personal feelings. Daily reading is part of the educational sphere. It is a public genre with diary elements. We can define it then as a text written in the first person singular, from pre-established by the teacher instructions. In it, the reader, as we read, reflectively dialogues with the text read, can evoke his repertoire readings and experiences. Primarily, the survey drew on theoretical assumptions Machado (1998), Buzzo (2010), Lejeune (2008) Cosson (2014b), Fish (1992), Compagnon (1999) Rouxel (2013) and Langlade (2013) . We analyzed four inputs of the students, after reading two short stories "The Head", Luiz Vilela (2006) and "To win the game," Rubem Fonseca (2002). These, according reread instrumentation for reinterpretation via crossing with other languages (music and film), presentation of data / images of the authors and contact with literary criticism. The productions of the students had as an analytical criterion the four items of pre-established teaching guidance for the preparation of records (first and third records), as well as criteria related to reinterpretation (second and fourth records). The results showed a more protagonist student-reader who is responsible for the construction of meanings of the texts read. They pointed out, along with the formal data and literary text content, the subjective intervention of readers linked to construction and / or identity-building (s). The students records also showed gaps, problems whose teaching intervention is imperative by proposing solutions and / or reflections on the understanding of the listed phenomena. Finally, we inferred that there was in the process of reading the students a combination of personal and social levels.